Ensino de biologia e a concepção de vida - Silva, Andrigéssica Mota da (2020)
The idea of Life is a topic widely discussed by biologists and researchers in general, in view of the difficulty of a concept that covers the breadth that this subject requires. The objective of this research is to understand the conception of life from the way it has been taught in the 1st year of high school. The research presents a qualitative approach of descriptive and analytical nature. The methodological path used participant observation, questionnaire and documentary analysis, field visits and the phenomenological method to describe the students' experiences in the Sumaúma State Park as data collection techniques. The data were analyzing the data by Bardin's Content Analysis. The first chapter approaches in a panoramic way the history of science in the search to understand how life is understood and its implications in the teaching of Biology, with a view to its implications in high school. The second chapter describes the desired methodological path. In the last chapter, we presented the conceptions of biology students of the 1st year of high school on the theme of life the development of activities having as background the Sumaúma State Park to contribute to the expansion of the representations that students have about the theme life. It is concluded that it is necessary to broaden the discussion beyond biological conception. Therefore, it is necessary to reflect on what life is in a philosophical, historical and religious conception absent in textbooks, whose answers given by the students show us the importance of this expansion. Keywords: Teaching of living, living beings, Sumaúma Park, study of living beings. Life.